Portadores nasales de S. aureus en el personal de enfermería de un centro de salud del Estado Carabobo, Venezuela - Capozzi E; Mobilit D; Martinez I (Kasmera, 2015)
Abstract: Staphylococcus aureus has been a problem in the area of health, for their behavior in immunosuppressed patients and bacterial resistance has developed in recent decades. It is common that the source of infection be health personnel, hence the knowledge of risk factors and the presence of allergic diseases could prevent nasal colonization of health personnel and subsequent transmission to hospitalized patients. It was a descriptive, not experimental and cross section research to assess the frequency of nasal carriage of Staphylococcus aureus in nursing staff of health center from Carabobo state. The sample consisted of 30 nurses, where 50% (15) were not carriers of this organism, 27% (7) carriers SAMS, and 23% (7) carriers of MRSA, 8 patterns of antibiotic resistance were detected, of which highlights resistance, to oxacillin, cefoxitin, clindamycin, erythromycin, ciprofloxacin, statistically significant association (p = 0.0001) between Staphylococcus aureus nasal carriage and the presence of a history of allergic diseases is obtained, thus can be considered that the presence of these pathologies is a risk factor of nasal colonization.